Pengembangan Perangkat Pembelajaran IPA SMP Berbasis Kooperatif Tipe STAD (Student Teams Achievement Division) Pada Materi Pemanasan Global - Noer Layli Isro'iyah; Nindha Ayu Berlianti; Nur Kuswanti (Wacana Didaktika, 2022)
This research is a development research whit the aim of developing a cooperative learning device based on the STAD (Student Teams Achievement Division) type. In this learning device, what was developed was the Learning Implementation Plan (RPP) which was equipped whit a student worksheet (LKPD). In the development of this device using the ADDIE development model. This development stage consists of analysis (analysis), design (design), development (development), implementation (implementation) and evaluation (evaluation). However, at the implementation stage, the research was not carried out due to the Covid-19 situation. The result of the development research show that the validity of the STAD cooperative-based junior high school science learning tool on global warming material gets validation results in the “very valid” category with an average score of 4,5 out of a maximum is a complete lesson plan. Whit this LKPD is already feasible to use. Key words : Learning tools, STAD type cooperative, ADDIE, and science learning Abstrak: Penelitian ini merupakan penelitian pengembangan denga tujuan untuk mengembangkan perangkat pembelajaran berbasis kooperati tipe STAD (Student Teams Achievement Division). Pada perangkat pembelajaran ini, yang kembangkan yaitu Rencana Pelaksanaan Pembelajaran (RPP) yang dilengkapi dengan lembar kerja peserta didik (LKPD). Dalam pengembangan perangkat ini menggunakan model pengembangan ADDIE. Tahap pengembangan ini terdiri dari analisis (analysis), perancangan (design), pengembangan (development), implementasi (implementation) dan evaluasi (evaluation). Akan tetapi pada tahap implementation meneliti tidak dilakukan karena terkendala keadaan covid 19. Hasil dari penelitian pengembangan menunjukkan bahwa kevalidan perangkat pembelajaran IPA SMP berbasis kooperatif tipe STAD pada materi pemanasan global mendapatkan hasil validasi dalam kategori “sangat valid” dengan skor rata-rata 4,5 dari skor maksimal 5. Sehingga perangkat pembelajaran yang dikembangkan berupa RPP yang lengkapi dengan LKPD ini sudah layak digunakan.